Mobile Social Networking Role in Reconstruction and the Formation of Cultural Identity - Religion of Members - Forouzan, Younes; Homayoun, Mohammad Hadi; Zadeh, Seyyed Mohammad Mahdi; Shahabi, Mahmoud (International Review of Management and Marketing, 2018)
The main objective of this study was to determine the role of mobile social networks in the reconstruction and development of cultural-religious identity of users. The methodology of “grounded theory” has been chosen for this purpose. The present data was collected from 31 semi-structured interviews with active users of mobile social network and using open coding, axial and selective, was analyzed using a grounded theory approach. General classes identified in this study include characteristics of “indifference, lack of logical thinking, extremes of knowledge, lack of religious knowledge, divine insight, truth, belief de-religious, anti-religious beliefs injection; negative rating; a lack of belief hereafter, induction material retardation, mental confusion, impiety, overconfidence, religious communication, sincerity, personal management, family relationships instability; promoting anti-religious ethics, lack of pragmatism; lack of religious knowledge; the practice of religious orders, and to strengthen religious beliefs; sloth in the guise of religion; oversimplification religious orders, illegality, confusion, social system, education and government control, the destruction of social identity, crisis of identity (identity divergence); convergence of identity, cultural transformation “is, and also identify the central idea in this study that yielded the most stressed in the comments, “the transformation of cultural identity - religion.” Each of these dimensions in five “categories,” each with a specific role and status were classified as follows: (1) The effective variables, (2) variables underlying, (3) strategies, (4) performance and results, (5) reconstruction of religious and cultural identity formation. The outcome of this study was to develop “cultural-religious identity formation and regeneration of mobile social network users” is expected to improve its understanding of cultural-religious orientation efficient and effective. Keywords: Social Networks, Identity, Culture, Religion, Society JEL Classifications: L1, M14, Z12